"The Spanish Fury": A political geography of soccer in Spain. (March 2015) - Vaczi, Mariann
Soccer in Spain functions as a powerful ideological apparatus. Historically, the under-performance of the national selection ("Spanish Fury") was attributed to a lack of patriotism on part of players from ethno-regional peripheries. The recent successes (2008, 2012 Euro Cup and 2010 World Cup) of Spanish soccer are hailed as proof of a modern country that has finally overcome its regional divisions. Or has it? This article will explore soccer as a contested ideological terrain between Spanish, Basque and Catalan nationalism. The peripheries have been instrumental in the development of Spanish soccer and the "Spanish Fury, " as I will show in this paper, while they remain at odds with the idea of a central "Spain." This paper explores soccer as a schismogenic system of integration and disintegration that affect center–periphery relationships. I will explore the historical-particular mechanisms, achievements and impasses of ethnic, racial and national identity construction in three epochs: the pre-Franco dictatorship, when soccer was established as the hegemonic sports culture; the Franco dictatorship, an era of intensive homogenization; and the current democratic era in a supra-national Europe, where the peripheries emerge with renewed separatist energies.